Performance Analysis of Non-Communicable Disease Integrated Care Post Cadres at Community Health Centres - Hidayati, Wahyu; Lilis Suryani; Arie Wahyudi; Ali Harokan (Lentera Perawat, 2024)
The implementation of the Posbindu PTM programme encounters many obstacles such as insufficient facilities and infrastructure, lack of training and limited human resources, This study aims to determine the factors associated with the performance of Posbindu PTM cadres at the Martapura Health Centre. This research is quantitative with a crossectional approach.  The population of this study were cadres Posbindu PTM in Martapura Year 2024. The sample in this study amounted to 60 people. The sampling method uses total sampling. This research was conducted on 22 February - 15 March 2024. Data collection techniques by interview using a questionnaire. Bivariate data analysis using Chi-Square test and multivariate using logistic regression test. The results showed that there was a relationship between motivation (p value 0.006) and training (p value 0.00) on the performance of NCD posbindu cadres at Puskesmas Martapura, East Ogan Komering Ulu Regency in 2024. There is no relationship between age (p value 0.59), attitude (p value 0.21) and supervision (p value 0.46) to the performance of NCD posbindu cadres at Puskesmas Martapura, East Ogan Komering Ulu Regency in 2024. The most dominant factor with the performance of cadres posbindu NCD at Puskesmas Martapura East Ogan Komering Ulu Regency Year 2024 is motivation (p value 0.004) (Odds Ratio 0.179). Conclusion there is a relationship between motivation and training on the performance of cadres posbindu NCD at Puskesmas Martapura East Ogan Komering Ulu Regency Year 2024. Suggestions for Puskesmas should provide motivation to cadres posbindu PTM, such as giving appreciation or reward to cadres who excel.